The protective effect of curcumin on the diabetic uterus: Quantitative and qualitative evaluation - Mutlu, Ayşenur Kaya; Tüfekci, Kıymet Kübra; Kaplan, Süleyman (Elsevier BV, 2025)
The objective of this study was to examine the impact of diabetes on the rat uterus and to assess the potential therapeutic benefits of curcumin in a diabetic uterus.A total of thirty-eight female Wistar albino rats were randomly assigned to seven experimental groups. The control group (Cont) was not subjected to any treatment. The sham group (Sham) was administered corn oil, while the curcumin group (Curc) received 30 mg/kg curcumin. A single dose of 50 mg/kg streptozotocin (STZ) was administered to induce experimental diabetes. The diabetic animals were then divided into four groups: a group with diabetes mellitus (DM), a group administered curcumin after seven days of diabetes induced (DC1) and 21 days (DC2) after the onset of diabetes, and a group that received curcumin simultaneously with STZ (DC3). The Cavalieri's method was used to estimate the volume ratios of the uterine epithelium, layers, and blood vessels.The volume ratio of the myometrium was observed to be higher in the DC2 group than in the Cont and DM groups. Conversely, the endometrial volume ratio was found to be lower in the DC2 group than in the Cont group. The cell borders and basement membranes of the epithelial and gland cells were well preserved in the curcumin treatment groups, despite the obvious damage observed in the DM group. Similar findings were also observed in the electron microscopic sections, with collagen fibers, which were arranged in thick bands in the DM group and were unable to maintain their ultrastructure, were well organized in the DC1, DC2, and DC3.Considering that it improves the endometrial structure and reduces degeneration in the surface and gland epithelium, it can be said that curcumin is an effective agent in reducing and preventing complications associated with DM in the uterus.
Keywords: Endometrium; Curcumin; Uterus; Animals; Female; Rats, Wistar; Diabetes Mellitus, Experimental; Rats